Openness and Agricultural Performance in Nigeria - Inusa, Eshiozemhe Micheal; Umaru, Aminu (Asian Journal of Economic Modelling, 2021)
The paper examined the effect of openness on agricultural output in Nigeria. Data for the study was sourced from CBN statistical bulletin 2019 and quarterly report 2020 covering the period 2010Q1 to 2020Q2. ADF unit root test, Johansen cointegration and Autoregressive Distributed Lag Methods were employed in the study. The unit root test results revealed that the variables are a mixture of I(1) and I(0) order of integration. Empirical result of the study shows that increase in trade openness will lead to a positive but insignificant increase in agricultural output while increase in financial openness will lead to a significant decrease in agricultural output in the country. The study concluded that trade openness affect agricultural output positively, while financial openness affect agricultural output negatively. The study therefore recommended that efforts should be put in place to ensure that trade openness is encouraged, also, government and relevant stakeholders in agricultural sector should make sure that foreign direct investment to agricultural sector are accountable and properly utilized in the sector.